Strategic planning in governmental hospitals in the southern governorates of Palestine – An applied study on a sample of hospitals 2009 – 2019 – - Aburahma, AbdalBaset Hasan (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the degree of strategic planning practice in a sample of government hospitals, in the southern governorates of Palestine, and the researcher used the descriptive and analytical approach. Among the most important results of the study is that the degree of application of strategic planning dimensions was medium, with a relative weight of 63.37%, and the results showed that there are no statistically significant differences between the responses of the study sample members to the degree of strategic planning practice due to the variable of gender, academic qualification, number of years of service, and the presence of statistically significant differences attributable to the variables of the workplace and the current job, and among the most important recommendations of the study: the necessity of establishing specific and systematic mechanisms that include Broader participation of the hospital's internal and external community when formulating the vision and mission of the hospital, and recommended arranging the strategic objectives according to the priority that the hospital can achieve, providing the necessary financial and material resources for them, at least 2.5% of the hospital’s budget, and recommending an annual periodic review of the strategic plan.
Keywords: strategic planning; government hospitals; southern governorates of Palestine